Detecting substrate glycans of fucosyltransferases with fluorophore-conjugated fucose and methods for glycan electrophoresis. (2nd May 2020) - Wu, Zhengliang L; Whittaker, Mark; Ertelt, James M; Person, Anthony D; Kalabokis, Vassili
Abstract: Like sialylation, fucose usually locates at the nonreducing ends of various glycans on glycoproteins and constitutes important glycan epitopes. Detecting the substrate glycans of fucosyltransferases is important for understanding how these glycan epitopes are regulated in response to different growth conditions and external stimuli. Here we report the detection of these glycans on glycoproteins as well as in their free forms via enzymatic incorporation of fluorophore-conjugated fucose using FUT2, FUT6, FUT7, FUT8 and FUT9. Specifically, we describe the detection of the substrate glycans of these enzymes on fetal bovine fetuin, recombinant H1N1 viral neuraminidase and therapeutic antibodies. The detected glycans include complex and high-mannose N-glycans. By establishing a series of precursors for the synthesis of Lewis X and sialyl Lewis X structures, we not only provide convenient electrophoresis methods for studying glycosylation but also demonstrate the substrate specificities and some kinetic features of these enzymes. Our results support the notion that fucosyltransferases are key targets for regulating the synthesis of Lewis X and sialyl Lewis X structures.